치과공포감과 주관적인 구강건강관련 삶의 질과의 관련성 - 이경희; Kyeong Hee Lee; 김소라; So Ra Kim; 구지혜; Ji Hye Gu; 김찬주; Chan Ju Kim; 최다혜; Da Hye Choi (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of the study is to investigate the relationship between dental fear and subjective oral health-related quality of life. Methods: A self-reported questionnaire was filled out by 320 subjects in Seoul and Gyeonggido from June to August, 2014 after permission from Institutional Review Board (IRB). Except incomplete 9 copies, 311 data were analyzed using SPSS WIN 19.0 program. The questionnaire consisted of five questions of the general characteristics of the subjects, twelve questions of oral health related quality of life, eighteen questions of dental fear, and one question of awareness toward subjective health status. Results: The explanation power of subjective oral health-related quality of life on dental fear was 26.2 percent. As the subjective oral health-related quality of life increased by 1 point, the dental fear decreased at the rate of 0.645 (p<0.001). Conclusions: Higher subjective oral health-related quality of life will diminish the dental fear. Regular dental checkups and preventive treatment are very important to enhance the oral health-related quality of life in those who visit the dental clinic.